Recycling method of magnesium smelting byproduct magnesium waste residue
By mixing magnesium slag micro powder with valine aqueous solution, and performing natural curing and carbonization of low-concentration carbon dioxide, the problem of magnesium waste slag utilization in magnesium smelting was successfully solved, and efficient recycling and reuse of magnesium slag and flue gas carbon dioxide was achieved, and a high-strength, environmentally friendly magnesium slag carbon-solid gelling material was prepared.
Patent Information
- Application Number
- CN202411944905.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to effectively utilize the magnesium waste slag generated in magnesium smelting, and it is difficult to achieve in-situ digestion and recovery of magnesium slag and flue gas carbon dioxide in a low-concentration carbon dioxide environment.
By mixing the magnesium slag micro powder with valine aqueous solution, it is converted into a magnesium slag carbon-solid gelling material after natural curing and carbonization of low-concentration carbon dioxide.
It realizes efficient recycling and reuse of magnesium slag, and prepares high-strength, low-cost, and environmentally friendly magnesium slag carbon-solid gelling materials, solving the in-situ digestion and recycling of magnesium slag and flue gas carbon dioxide.
Smart Images

Figure CN119638231A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of industrial by-product waste recycling technology, specifically, it relates to a method for recycling and reusing magnesium slag, a by-product of magnesium smelting. Background Technology
[0002] Magnesium reduction slag is a solid waste generated during the industrial smelting of primary magnesium. It is highly hygroscopic, and its indiscriminate accumulation can easily lead to soil salinization and compaction, polluting the environment. China is the world's largest producer of primary magnesium, producing approximately 1 million tons annually. However, smelting 1 ton of primary magnesium produces 6.5 to 8 tons of magnesium reduction slag and over 20 tons of flue gas carbon dioxide. The contradiction between high magnesium slag emissions and low comprehensive utilization rate has been a significant factor restricting China's further increase in primary magnesium production capacity. Meanwhile, as a major energy consumer and cement producer, my country's current industrial development still relies heavily on traditional fossil fuels, and achieving the emission reduction target of "carbon peaking and carbon neutrality" remains a significant challenge.
[0003] Currently, there is limited research and application of magnesium slag. Due to its low early hydration activity and slow reaction rate, magnesium slag has a low substitution rate when used as a mineral admixture to prepare cement-based cementitious materials. On the one hand, the dosage is usually less than 30%. On the other hand, the addition of magnesium slag significantly reduces the compressive strength of cementitious materials, which restricts its application scenarios.
[0004] Carbon dioxide curing technology is an important way to improve the utilization rate of magnesium slag. Currently, the gas commonly used in the curing process is high-concentration carbon dioxide with a concentration of 99%. On the one hand, due to the large specific surface area and fineness of magnesium slag, the products made from it are prone to rapidly forming a closed calcite-type calcium carbonate product layer on the surface during the high-concentration, high-pressure carbonation curing process. This hinders the subsequent introduction of gas, resulting in the magnesium slag inside the product not fully reacting with carbon dioxide, which greatly restricts the development of product strength. On the other hand, the concentration of the high-concentration carbon dioxide mentioned above is very different from the concentration of carbon dioxide in the flue gas actually emitted by the factory (generally not exceeding 20%). If this part of the flue gas carbon dioxide needs to be utilized, it also needs to be compressed and purified, increasing costs and process complexity. Therefore, the current methods for reusing magnesium slag are not conducive to achieving the in-situ digestion and recovery of by-product magnesium slag and flue gas carbon dioxide.
[0005] Therefore, how to utilize large quantities of magnesium slag, a bulk solid waste, efficiently and effectively in a low-concentration carbon dioxide environment, to achieve both solid waste and carbon sequestration applications still requires continuous research and technological improvement. Summary of the Invention
[0006] To address the problem of the inability to rationally reuse magnesium slag, a byproduct of magnesium smelting, in existing technologies, the inventors of this invention, based on long-term research into the carbonization reaction mechanism of magnesium slag, have proposed a novel method for recycling and reusing waste slag from magnesium smelting. This recycling method can directly transform magnesium slag into a magnesium slag carbon-fixing cementitious material under the action of specific amino acids, and has advantages such as simple process, short production cycle, high solid waste utilization rate, and environmental friendliness.
[0007] The present invention specifically adopts the following technical solution:
[0008] A method for recycling and reusing magnesium waste slag, a byproduct of magnesium smelting, comprising the following steps:
[0009] S1. Prepare valine into an aqueous solution;
[0010] S2. Mix the magnesium slag powder with the above-mentioned valine aqueous solution and stir to form a slurry;
[0011] S3. The slurry is molded into a sample and then naturally cured.
[0012] S4. The naturally cured samples are subjected to carbonization curing to obtain magnesium slag carbon-fixing cementitious materials.
[0013] In step S1, the concentration of the valine aqueous solution is 0.25 mol / L to 1 mol / L.
[0014] In step S2, the mass ratio of valine aqueous solution to magnesium slag powder is 0.3:1 to 0.4:1.
[0015] Furthermore, magnesium slag powder is a powder with a particle size of less than 0.15 mm obtained by ball milling the waste slag from industrial magnesium smelting reduction.
[0016] Generally, in step S3, the natural curing conditions are: temperature of 18℃~22℃, humidity of 40%~60%, and time of 18h~20h.
[0017] In step S4, the conditions for carbonization curing are as follows: the volume concentration of CO2 used for carbonization curing does not exceed 20%, the curing pressure is 0.05MPa to 0.1MPa, and the curing time is 4h to 6h.
[0018] Furthermore, the CO2 used for carbonization curing is carbon dioxide from the flue gas produced as a byproduct of industrial magnesium smelting.
[0019] The recycling method provided by this invention, firstly, utilizes valine to directly promote the dissolution of calcium ions in magnesium slag powder and possesses high hydrophilicity, enabling it to bind water molecules. Based on this, and combined with the carbonation curing process, the dissolved calcium ions and carbonate ions generated from the dissolution of carbon dioxide in water combine to form more stable carbonation products—amorphous calcium carbonate (ACC). Simultaneously, valine can act as a nucleation site, generating the aforementioned amorphous calcium carbonate in situ. This results in the formation of more highly dense and gelling organic-inorganic composite carbonation products within the final magnesium slag carbon-fixing cementitious material, significantly improving the product's strength. In other words, valine regulates the crystal form, morphology, and structure of the carbonation products in this reaction system, inducing the formation of gelling organic-inorganic composite calcium carbonate, thereby significantly improving the strength of the magnesium slag carbon-fixing cementitious material. Secondly, during carbonization curing, a low-concentration carbon source with a CO2 concentration not exceeding 20% is selected, and carbonization curing is carried out under low pressure. This avoids the problem of a closed calcite-type calcium carbonate product layer easily forming on the surface during high-concentration, high-pressure carbonization curing, which hinders the development of product strength. Furthermore, it eliminates the need for a pressing and molding process, resulting in low cost and low energy consumption. Moreover, the low-concentration carbon source can be flue gas carbon dioxide, thus achieving in-situ decomposition of magnesium slag and flue gas carbon dioxide, making the comprehensive recycling and reuse of by-product waste gas and slag from magnesium smelting more practical. Thirdly, the above-mentioned recycling and reuse method of this invention utilizes only the aforementioned effects of valine to prepare high-strength magnesium slag carbon-fixing cementitious materials, achieving recycling and reuse without the need for SiO2 or other components to activate its pozzolanic effect to improve product strength, nor for other additional functional components. Furthermore, the finished product does not need to react with cement or other basic cementitious materials, offering the advantage of a simple process. Attached Figure Description
[0020] Figure 1 This is a SEM image of the interior of the magnesium slag carbon-fixing cementitious material prepared according to Example 1 of the present invention;
[0021] Figure 2 These are SEM and EDS images of the interior of the magnesium slag carbon-fixing cementitious material prepared according to Example 3 of the present invention.
[0022] Figure 3 These are SEM and EDS images of the interior of the comparative cementitious material prepared in Comparative Example 2 according to the present invention;
[0023] Figure 4 These are SEM and EDS images of the interior of the comparative cementitious material prepared in Comparative Example 4 according to the present invention. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0025] Example 1
[0026] This embodiment provides a method for the comprehensive utilization of waste gas and slag from magnesium smelting, including the following steps:
[0027] (1) Grind magnesium slag into magnesium slag powder with a particle size of less than 0.15 mm, dissolve valine in deionized water to prepare a valine solution of 0.25 mol / L, and prepare materials according to the mass ratio of magnesium slag powder to valine solution of 10:4.
[0028] (2) Mix the components and stir evenly to obtain a slurry, and then mold it in a mold.
[0029] (3) After the slurry is formed, it is naturally cured at a temperature of 20±2℃ and a humidity of 40% to 60% for 18 to 20 hours before demolding to obtain the sample.
[0030] (4) Place the demolded sample into a carbonization reaction pressure vessel, then evacuate the pressure vessel and introduce 20% concentration of flue gas carbon dioxide to a carbonization pressure of 0.10 MPa. Carbonize and cure for 4 hours to obtain magnesium slag solid carbon cementitious material.
[0031] It should be noted that in this step, the pressure vessel for the carbonization reaction is typically filled with gas to 0.10 MPa and then the valve and vent are closed to prevent gas leakage. As the carbonization reaction proceeds, the pressure gradually decreases. When it drops to no less than 0.05 MPa, the valve needs to be reopened to fill the vessel again to no more than 0.10 MPa. This process is repeated until the total carbonization curing time is reached. Therefore, the entire carbonization curing process is carried out during pressure changes between 0.05 MPa and 0.10 MPa, rather than maintaining a constant reaction pressure.
[0032] According to GB / T 17671 "Test Method for Strength of Cement Mortar", its compressive strength was measured to be 16.97 MPa.
[0033] The internal structure of the magnesium slag carbon-fixing cementitious material obtained above was subjected to SEM testing, such as... Figure 1 As shown. From Figure 1 As can be seen, the carbonization products generated based on valine inducement exhibit obvious gelling and continuous characteristics.
[0034] Example 2
[0035] The similarities between this embodiment and Example 1 will not be repeated here; only the differences from Example 1 will be described. The difference between this embodiment and Example 1 is that the concentration of the prepared valine solution is 0.50 mol / L; the rest is the same as in Example 1, to obtain the magnesium slag carbon-fixing cementitious material.
[0036] The strength of the obtained magnesium slag carbon-fixing cementitious material was tested, and its compressive strength was measured to be 24.54 MPa.
[0037] Example 3
[0038] The similarities between this embodiment and Example 1 will not be repeated here; only the differences from Example 1 will be described. The difference between this embodiment and Example 1 is that the concentration of the valine solution prepared is 1.00 mol / L; the rest is the same as in Example 1, to obtain the magnesium slag carbon-fixing cementitious material.
[0039] The obtained magnesium slag carbon-fixing cementitious material was subjected to strength testing, and its compressive strength was measured to be 34.02 MPa.
[0040] The internal structure of the magnesium slag carbon-fixing cementitious material obtained above was subjected to SEM testing, such as... Figure 2 As shown on the left, the carbonization products induced by valine exhibit obvious gelling and continuous characteristics.
[0041] At the same time, targeting Figure 2 EDS energy dispersive spectroscopy was performed on the area within the box in the SEM image, such as... Figure 2 As shown on the right. According to EDS energy dispersive spectroscopy, the carbonized product layer contains not only the elements Ca, C, and O found in calcium carbonate, but also the characteristic element N of valine. Therefore, this gelling, stronger carbonized product layer is induced by valine.
[0042] Example 4
[0043] The similarities between this embodiment and Example 3 will not be repeated here; only the differences from Example 3 will be described. The difference between this embodiment and Example 3 is that the materials are prepared according to a mass ratio of magnesium slag powder to valine solution of 10:3, and carbonized and cured for 6 hours; the rest is the same as in Example 3, to obtain magnesium slag carbon-fixing cementitious material.
[0044] The strength of the obtained magnesium slag carbon-fixing cementitious material was tested, and its compressive strength was measured to be 30.13 MPa.
[0045] To verify the necessity of the process in the above-described recycling method of the present invention, several comparative experiments were conducted.
[0046] Comparative Example 1
[0047] The similarities between this comparative example and Example 3 will not be repeated here; only the differences between them will be described. The difference between this comparative example and Example 3 is that step (4) carbonization curing is not performed. Instead, natural curing is continued for 7 days at a temperature of 20±2℃ and a humidity of 40% to 60% to obtain the first comparative magnesium slag carbon-fixing cementitious material.
[0048] The strength of the obtained magnesium slag carbon-fixing cementitious material was tested, and its compressive strength was measured to be 0.71 MPa.
[0049] Comparative Example 2
[0050] The similarities between this comparative example and the embodiment will not be repeated here; only the differences from Embodiment 1 will be described. The difference between this comparative example and Embodiment 1 is that an equal amount of deionized water is used to replace the valine solution in mixing the magnesium slag powder to obtain the second comparative magnesium slag carbon-fixing cementitious material.
[0051] The obtained magnesium slag carbon-fixing cementitious material was subjected to strength testing, and its compressive strength was measured to be 2.21 MPa.
[0052] SEM tests were performed on the interior of this magnesium slag carbon-fixing cementitious material, such as... Figure 3 As shown on the left. It can be seen that the magnesium slag carbonization cementitious material formed by mixing only deionized water produces a loose and porous carbonization product without cementing properties.
[0053] At the same time, targeting Figure 3 EDS energy dispersive spectroscopy was performed on the area within the box in the SEM image, such as... Figure 3 As shown on the right. According to EDS energy dispersive spectroscopy, the carbonized product does not contain the characteristic element N of amino acids, but only the corresponding elements Ca, Mg, Si, C, and O of the reactants and calcium carbonate. The strength of the resulting product is also significantly lower than that of the product prepared from valine solution in Example 3. This demonstrates that the addition of valine ultimately promotes an increase in product strength.
[0054] Comparative Example 3
[0055] The similarities between this comparative example and Example 3 will not be repeated here; only the differences from Example 3 will be described. The difference between this comparative example and Example 3 is that 99% CO2 concentration was used, and carbonization curing was carried out at a carbonization pressure of 0.2 MPa to obtain the third comparative magnesium slag carbon-fixing cementitious material.
[0056] The obtained magnesium slag carbon-fixing cementitious material was subjected to strength testing, and its compressive strength was measured to be 16.89 MPa. This is because the high concentration of carbon dioxide and the high pressure carbonization environment cause a closed calcite product layer to form too quickly on the surface of the magnesium slag product, which is not conducive to the continuous carbonization reaction. The interior of the product cannot fully participate in the reaction, hindering the formation of organic-inorganic composite carbonization products. Under these circumstances, valine, as an organic component inside the product, actually affects the strength of the product, leading to a decrease in strength.
[0057] Comparative Example 4
[0058] The similarities between this comparative example and Example 3 will not be repeated here; only the differences from Example 3 will be described. The difference between this comparative example and Example 3 is that an equal amount of 1.00 mol / L serine solution was used instead of valine solution to mix the magnesium slag powder, resulting in the fourth comparative magnesium slag carbon-fixing cementitious material.
[0059] The strength of the obtained magnesium slag carbon-fixing cementitious material was tested, and its compressive strength was measured to be 14.22 MPa.
[0060] SEM tests were performed on the interior of this magnesium slag carbon-fixing cementitious material, such as... Figure 4 As shown on the left. It is evident that serine induces the formation of predominantly spherical aragonite-type calcium carbonate within the product, rather than... Figure 1 and Figure 2 The continuous and dense amorphous calcium carbonate on the left has a much weaker gelling and pore-filling effect than the latter. This also leads to the product strength of Comparative Example 4 being much lower than that of Example 3. This further proves that the organic-inorganic composite carbonization product with amorphous calcium carbonate as the main component induced by valine is more conducive to improving the applicability of magnesium slag carbon-fixing cementitious materials.
[0061] It can also be seen that the recycling method of the present invention uses valine, which plays a key role in obtaining a product with higher strength, while other amino acids such as serine, which are also common amino acids, cannot play a similar role. This valine is not an arbitrary selection of amino acids.
[0062] The mass changes of the main reactants and main products involved in Examples 2, 3 and Comparative Example 2 were tested, as shown in Table 1 below.
[0063] Table 1. Mass changes of major reactants and products in Examples 2, 3 and Comparative Example 2.
[0064]
[0065]
[0066] The data in Table 1 show that the addition of valine significantly induced the formation of amorphous calcium carbonate in magnesium slag carbon-fixing cementitious materials, i.e. Figure 1 and Figure 2 The layer of cementitious calcium carbonate products formed on the left.
[0067] In addition, to explore the mechanism of action of valine on magnesium slag powder in the above embodiments, the inventors of this invention also conducted the following tests: the slurries obtained by mixing magnesium slag powder and valine solution in Examples 2 and 3 above, and the slurry obtained by mixing magnesium slag powder and water in Comparative Example 2 were diluted respectively, the supernatant was collected by centrifugation, and the calcium ion content was quantitatively tested by inductively coupled plasma atomic emission spectrometry. The test results are shown in Table 2 below.
[0068] Table 2 shows the calcium ion content in magnesium slag micronized slurry in Examples 2 and 3 and Comparative Example 2.
[0069]
[0070] As can be seen from the calcium ion concentration data in Table 2, the addition of valine can exponentially increase the leaching amount of calcium ions from magnesium slag. The reason for this is likely that the organic functional groups (-CH3, -NH2, -COOH) in valine induce greater leaching of positively charged calcium ions from the magnesium slag through charge attraction.
[0071] In summary, in the recycling and reuse methods provided in the above embodiments, valine can not only directly promote the dissolution of calcium ions in magnesium slag, but also act as a nucleation site to induce the generation of organic-inorganic carbonization products, thereby exhibiting stronger product strength.
[0072] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for recycling magnesium waste slag produced as a by-product of magnesium smelting, characterized in that: The steps include: S1, preparing valine into a valine aqueous solution with a concentration of 0.25 mol / L to 1 mol / L; S2, mixing the magnesium slag powder and the valine aqueous solution in a mass ratio of 1:0.3 to 1:0.4, and stirring into a slurry; S3, forming the slurry into a sample and performing natural curing; S4. Carry out carbonization curing for 4 h to 6 h on the naturally cured sample at a CO2 volume concentration not exceeding 20% and a pressure of 0.05 MPa to 0.1 MPa to obtain a magnesium slag carbon-fixing cementitious material.
2. The recycling method according to claim 1, characterized in that: In step S4, the CO2 used for carbonization maintenance is carbon dioxide from flue gas produced as a by-product of industrial magnesium smelting.
3. The recycling method according to claim 1 or 2, characterized in that: In step S2, the magnesium slag powder is a powder with a particle size less than 0.15 mm obtained by ball milling industrial magnesium smelting reduction slag.
4. The recycling method according to claim 3, characterized in that: In step S3, the natural curing conditions are: temperature of 18°C to 22°C, humidity of 40% to 60%, and time of 18h to 20h.